The Impact of the Family Environment on Students' Interest in Entrepreneurship with Entrepreneurial Motivation as an Intervening Variable (Case Study on Students in Medan City) - Wendari, Radinka Maura; Putra, Rizki; Ardiani, Winda (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to examine the impact of the family environment on entrepreneurial motivation and to determine the partial influence of both the family environment and entrepreneurial motivation on students' interest in entrepreneurship. Additionally, the study explores how the family environment influences students' entrepreneurial interest through entrepreneurial motivation in Medan City. Since the population is not precisely known, the study employs the MOE formula to determine the sample size, resulting in 100 participants. The sampling technique used is purposive sampling, and path analysis is applied for data analysis. The study's findings indicate that the family environment The influence of entrepreneurial motivation on students' interest in entrepreneurship is both positive and significant, while the family environment also plays a crucial role, positively impacting both entrepreneurial motivation and students' interest in entrepreneurship through the mediation of entrepreneurial motivation.